Wegbeschreibungen in Reiseberichten des Mittelalters und der Frühen Neuzeit - Javor Briški, Marija (Ars et humanitas, 2018)
Based on the assumption that space is not objectively given and that its construction depends on the individual's perception, the author analyses two literary works, namely a late medieval pilgrimage travelogue by Konrad Grünemberg, and an educational travelogue by the Saxon nobleman Georg Christoph von Neitzschitz from the 17th century, whereby she uses mostly Certeau's theory of space. Taking into consideration the genres and author's intentions, she explores which conceptions of space are generated by path descriptions in the initial, transitional and destination space focusing on the relationship between the map and the parcours and selectively taking into account the relationship between the text and the visual materials.
Keywords: Frühe Neuzeit; Georg Christoph von Neitzschitz; koncepcija prostora; Konrad Grünemberg; Michel de Certeau; Mittelalter; Pilgerbericht; poti; potopis; Raumkonzeption; Reisebericht; romarski potopis; srednji vek; Wege; zgodnji novi vek